News Sites Speech Code: Presentation and Personalization - Akimova, Nataliia (East European Journal of Psycholinguistics, 2017)
The article is focused on how news site speech code elements are embodied by means of presentation and personalization. Among the main research methods are analysis and synthesis, descriptive text analysis, linguocultural and concept text analysis, modeling, method of semantic and pragmatic interpretations, contextual observation and comparative analysis are used. Definition of presentation and personalization are presented, examples of the most popular news sites of UKRNET (Korrespondent.net, LB.ua) and Runet (RosBusinessConsulting, RIA Novosti) are analyzed. Such problems are accented as how these features complicate news text understanding, what psychological and neurolinguistic difficulties they cause, what psycholinguistic mechanisms are involved in understanding process of these news announcements. Traditional communicative code is violated and the readers’ consciousness is manipulated. The user unknowingly pays attention to these texts, he spontaneously remembers them and then uses as a cliché or a model in his speech. Verbal behavior changes, in their turn, lead to changes in thinking and understanding of reality. The research is carried out in the context of the theory of deviant speech units, achievements of modern linguistics, cognitive science, psychology and neuroscience. References Akіmova, N. Movlennevі devіacії u movі ukraїns’kih іnternet-ZMІ: tendencіja movy epohi chi zasіb manіpuljuvannja [Speech deviation in the language of Ukrainian online media: the tendency of epoch’s language or means of manipulation]. Retrieved from http://mentalnist-2016.blogspot.com/p/blog-page_49.html. Kompantseva, L. (2007) Іnternet-Komunіkacіya: Kognіtyvno-Prahmatychnyi ta lіngvokul’turologіchnyi Aspekty [Internet Communication: Cognitive Pragmatic and Linguistic and Cultural Aspects] Extended Abstract of Doctoral dissertation. Kyiv. Filatova, O. G. (2004) Internet kak mass-media [Internet as a media]. Aktual’nye Problemy Teorii Kommunikacii, 232-240. Shchipitsyna, L. (2011). Kompleksnaya Lingvisticheskaya Kharakteristika KompyuternoOposredovannoy Kommunikacii (Na Materiale Nemetskogo Yazyka) [Complex Linguistic Features of Computer-Mediated Communication (Based on the German Language)]. Extended abstract of Doctoral dissertation. Voronezh. Sources Великий тлумачний словник сучасної української мови / В. Т. Бусел. Київ, Ірпінь: Перун, 2005. Velykyi Tlumachnyi Slovnyk Suchasnoї Ukraїns’koї Movy [Big Explanatory Dictionary of Contemporary Ukrainian]. (2005). V. Busel, Ed. Kyiv; Irpin: Perun. БТСРЯ – Большой толковый словарь русского языка / Гл. ред. С. А. Кузнецов. СПб. : Норинт, 2009. BTSRYA Bol’shoj Tolkovyj Slovar’ RusskogoYazyka [Big Explanatory Dictionary of Russian]. (2009). S. Kuznetsov, (Ed.). S.-Petersburg: Norint. LB.ua – Новини України від LB.ua: оперативна аналітика української політики, економіки, новини культури та спорту. Retrieved from: http://ukr.lb.ua/ Корреспондент.net – Останні новини України та світу. Корреспондент.net – свіжі новини дня. Retrieved from: http://korrespondent.net/Korrespondent.net РБК – РосБизнесКонсалтинг – новости, акции, курсы валют, погода, доллар, евро. Retrieved from: http://www.rbc.ru/ РИА – Главные новости часа. Лента новостей «РИА Новости». Retrieved from: http://ria.ru/